Development of an antibody-detection ELISA for Fasciola hepatica and its evaluation against a commercially available test. - Salimi-Bejestani, M.R. (2005)
An ELISA was developed for the detection of Fasciola hepatica antibody in serum of cattle. The assay was applied to sera from 258 naturally infected cattle, 256 non-infected cattle and six calves experimentally infected with F. hepatica. The diagnostic sensitivity and specificity of the ELISA test was 98% (95% confidence intervals, 96-100%) and 96% (95% confidence intervals, 93-98%) respectively at a cut-off value of 15% positivity. The results using sera from the experimentally infected calves showed that antibodies were first detected 2-4 weeks after infection. The ELISA test was also compared to the commercially available Bio-X bovine F. hepatica ELISA kit. A subset of 39 positive sera and 47 negative sera were selected from the samples used to evaluate the in-house test. The results indicated that the agreement between the two tests was almost perfect (k statistic=0.82).